Prevalence of colibacillosis in chickens in greater Mymensingh district of Bangladesh - Matin, Md. Abdul (Vet World, 2017)
AIM: This study was conducted for determination of the prevalence of colibacillosis in chicken in poultry farms in Mymensingh and Tangail districts. Isolation, identification, and antibiogram profile of Escherichia coli were also performed. MATERIALS AND METHODS: A total of 25 chickens manifested clinical signs of colibacillosis were collected from five different poultry farms during natural outbreaks. RESULTS: In broiler, the prevalence of colibacillosis was 0.84%, and in layer, prevalence was 0.80%. The prevalence of colibacillosis was 1.0% and 0.5% in 25-30 days old and 31-35 days old broiler, respectively. In case of layer birds, the prevalence was 0.6% in 40-45 days old bird and 1% in 46-50 days old bird. Identity of the E. coli isolate of chicken was confirmed by sugar fermentation, biochemical tests, and polymerase chain reaction assay. Antibiogram profile of E. coli isolate of chicken revealed that it was multidrug resistant (resistant against two antibiotics, such as ampicillin and cefalexin). CONCLUSION: Data of this study suggest that colibacillosis is prevalent in the study areas which underscore the need of implementation of prevention and control measure against this disease.